Assessing the role of field isolated Pseudomonas and Bacillus as growth‐promoting rizobacteria on avocado (Persea americana) seedlings - Solórzano Acosta, Richard Andi (2024)
This research aims to assess the efficacy of two genera of rhizobacteria from avocado field isolated: Pseudomonas and Bacillus, as plant growth‐promoting microorganisms in Hass avocado trees grafted onto Zutano rootstock.